Therapeutic Effect of Zingerone on Reproductive Damage in Diabetic Male Rats: Potential Role of Sirt1/Nrf2/HO-1 and Bax/Bcl-2 Signaling Pathways - Ekmen, Edanur Guler; Cay, Mehmet; Gungor, Ibrahim Halil; Ceribasi, Ali Osman (Wiley, 2026)
Diabetes mellitus exerts a deleterious effect on the male reproductive system, manifesting as a metabolic disease. Recent research has indicated that the ingestion of dietary supplements rich in natural antioxidants may reduce or prevent damage to the male reproductive system in cases of diabetes-induced infertility. This study investigated the effects of zingerone on diabetes-induced reproductive damage in male rats by analyzing the Sirt1/Nrf2/HO-1 signaling pathway, apoptosis, sperm quality, and histopathological changes. Seventy-five male Sprague Dawley rats, weighing between 250 and 300 g and aged 10 to 12 weeks, were divided into six groups. These included: control; zingerone (50 mg/kg); zingerone (100 mg/kg); diabetes; diabetes with zingerone (50 mg/kg); and diabetes with zingerone (100 mg/kg). Diabetes was induced via a single intraperitoneal injection of 55 mg/kg streptozotocin. Zingerone was given daily by oral gavage for a duration of 8 weeks. Results showed that zingerone significantly reduced glucose, MDA levels, and the Bax/Bcl-2 ratio, while markedly enhancing body weight, testosterone, GSH content, GSH-Px and CAT enzyme activity, and the expression of Sirt1, Nrf2, and HO-1. Additionally, it had a beneficial impact on spermatological parameters and histopathological findings in diabetic rats. The findings from this study, obtained from both healthy and diabetic rats, are consistent with each other, thereby providing a reliable basis for the conclusions drawn. Thus, incorporating zingerone into prophylactic regimens for healthy rats and therapeutic interventions for diabetic conditions may be advisable. Furthermore, combination drug therapies including zingerone may offer a viable approach to mitigating the toxic effects associated with certain drugs and to combating diabetes-related infertility. Consequently, it was concluded that zingerone ameliorates diabetes-induced damage to the male reproductive system, with 100 mg/kg zingerone demonstrating superior efficacy.
Keywords: Apoptosis; Diabetes; Oxidative Stress; Reproduction; Zingerone